Analisis dan Mitigasi Bencana Alam Kekeringan terhadap Kebutuhan Air Baku di Perumahan Antasari Permai Sukabumi Bandar Lampung - Sandya, I Gede Agung; Zain, Alfath; Jamaludin, Jamaludin (Universitas Batanghari Jambi, 2024)
This research aims to carry out a drought analysis of raw water needs in these settlements, as well as designing mitigation strategies to overcome this problem. The research method involves field surveys and drought index analysis using the Standardized Precipitation Index (SPI) method. The results of analysis using the SPI-3 and SPI-12 methods show that in the last 20 years the nature of the drought index in the Antasari Permai Housing Complex has been dominated by